COMPUTATIONAL MODELING OF LANGUAGE EVOLUTION: A STUDY OF DIACHRONIC LINGUISTICS (Contemporary Journal of Social Science Review, 2025)
This study explores the computational modeling of language evolution in Pakistan, focusing on the diachronic changes in regional languages due to language contact, particularly the influence of Urdu. Using agent-based models, evolutionary algorithms, and network theory, the researcher simulated the transmission and evolution of linguistic features, such as phonology, morphology, and syntax, across multiple generations. The study's primary aim was to understand how language shifts occur in multilingual societies, considering both social factors and government policies. By comparing the simulation results with historical data from archival materials and contemporary language surveys, the study identified key patterns in language change, particularly the role of Urdu in reshaping regional languages. The findings offer new insights into the mechanisms of language evolution and highlight the importance of social networks and language policies in shaping linguistic outcomes.